2018
DOI: 10.1089/end.2017.0855
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Urethral Lift: Does Size Matter?

Abstract: Early experience finds that a sufficient number of men with larger prostates appear to benefit from PUL. Patients with >80 g prostate size were more likely to have a median lobe and may benefit from resection of the median lobe at time of the PUL. Long-term follow-up is needed to evaluate the durability of the PUL procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…In their analysis of outcomes after Greenlight therapy, Pfitzenmaier et al report retreatment rates of 10.4 and 23.1% for patients with prostates < 80 and ≥ 80 cc, respectively [20]. Meanwhile, Shah et al reported retreatment after UroLift was 10% for SP men and 13% for LP men (median time to reintervention: 289 days) [21]. For broader context on retreatment after BPH MISTs, UroLift's original clinical trial had a two-year retreatment rate of 7.5%, while retreatments following prostatic arterial embolization have approached 20% [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of outcomes after Greenlight therapy, Pfitzenmaier et al report retreatment rates of 10.4 and 23.1% for patients with prostates < 80 and ≥ 80 cc, respectively [20]. Meanwhile, Shah et al reported retreatment after UroLift was 10% for SP men and 13% for LP men (median time to reintervention: 289 days) [21]. For broader context on retreatment after BPH MISTs, UroLift's original clinical trial had a two-year retreatment rate of 7.5%, while retreatments following prostatic arterial embolization have approached 20% [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A study including 23 patients with prostate volume of >80 g demonstrated significant improvement in AUA symptom score (AUASS) when compared to 51 men with <80 g prostates 61 . However, in this series, 22% of men with prostatic volume of >80 g were found to have a median lobe which required resection or ablation.…”
Section: Minimally Invasive Surgical Treatments (Mist)mentioning
confidence: 75%
“…This study was not conducted in the context of clinical trials, and the real-world BPH included a wide range of patient baseline values. Shah et al [49] evaluated whether the PUL procedure was also effective for larger prostates (prostate size >80 g) and considered that men with larger prostates appear to benefit from PUL. PUL durability in patients with prostate sizes >80 g requires longer follow-up data for assessment and validation.…”
Section: Discussionmentioning
confidence: 99%